We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.

1.) Find all pairs of real numbers $(x,y)$ such that $x + y = 6$ and $x^2 + y^2 = 28$. If you find more than one pair, then list your pairs in order by increasing $x$ value, separated by commas. For example, to enter the solutions $(2,4)$ and $(-3,9)$, you would enter "(-3,9),(2,4)" (without the quotation marks).


2.)The roots of the quadratic equation $z^2 + az + b = 0$ are $2 - 3i$ and $2 + 3i$. What is $a+b$?

 Apr 22, 2018

2.)The roots of the quadratic equation $z^2 + az + b = 0$ are $2 - 3i$ and $2 + 3i


The sum of the roots  =   -a / 1


(2 - 3i) + (2 + 3i)  = - a /1

4  =  -a

-4  = a


The product of the roots will  =  b /1


(2 - 3i) (2 + 3i)  =   b

4 + 9  = 13 = b


So....a + b  =   -4 + 13   =   9



cool cool cool

 Apr 22, 2018

Thank you!!

gueesstt  Apr 22, 2018

The first equation involves knowledge on how to solve system of equations. There is a chance that there will be two solutions here because the second equation \(x^2+y^2=28\) is a degree-two polynomial. I think it would be easiest to utilize the substitution method here.


\(x+y=6\) I will solve for x, but you could just as easily solve for y.


Since I know that x=6-y, I can substitute this information into the second equation \(x^2+y^2=28\).


\(x^2+y^2=28\) Substitute x for 6-y and solve the equation.
\((6-y)^2+y^2=28\) Let's expand the left hand side of the equation.
\(36-12y+y^2+y^2=28\) Let's do some rearranging and combining of like terms.
\(2y^2-12y+36=28\) Subtract 28 from both sides.
\(2y^2-12y+8=0\) Every term on the left hand side has a factor of 2, so let's fact that out!
\(2(y^2-6y+4)=0\) Unfortunately, the trinomial inside the parentheses is not factorable, so we will have to use alternate methods (like the quadratic formula) to figure out the roots of this equation.
\(a=1;b-6;c=4\\ y_{1,2}=\frac{-(-6)\pm\sqrt{(-6)^2-4(1)(4)}}{2(1)}\) The only thing to do now is simplify.
\(y_{1,2}=\frac{6\pm\sqrt{20}}{2}\) Let's simplify the radical completely.
\(y_{1,2}=\frac{6\pm2\sqrt{5}}{2}=3\pm\sqrt{5} \)  
\(y_1=3+\sqrt{5}\\ y_2=3-\sqrt{5}\) We now have to figure out what the corresponding x-values are. Let's use the first equation for that (\(x+y=6\)).


\(x_1+y_1=6\) Substitute the value for y_1 and solve for the remaining unknown.
\(x_1+3+\sqrt{5}=6\) Subtract 3
\(x_1+\sqrt{5}=3\) Subtract \(\sqrt{5}\)
\(x_1=3-\sqrt{5}\) Now, let's figure out the next x-value.
\(x_2+3-\sqrt{5}=6\) Now, do the same process.


Therefore, the two solutions for this system are \((3-\sqrt{5},3+\sqrt{5}),(3+\sqrt{5},3-\sqrt{5})\). This is just part one.

 Apr 22, 2018

Thank you!!

gueesstt  Apr 22, 2018

No problemo!

TheXSquaredFactor  Apr 22, 2018

15 Online Users